1982
DOI: 10.1210/jcem-54-4-725
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Androgen Receptor Deficiency in Infertile Men*

Abstract: To ascertain the frequency of androgen resistance as the cause of male infertility and to determine whether endocrine abnormalities are a universal feature of the disorder, we measured the androgen receptor in fibroblasts cultured from the genital skin of 28 unrelated phenotypically normal men with idiopathic azoospermia or oligospermia. The amounts of androgen receptor were compared with those in genital skin fibroblasts from a variety of other subjects, including 10 men with azoospermia of known cause, 5 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(42 citation statements)
references
References 28 publications
2
39
0
1
Order By: Relevance
“…There have been a few reports of abnormally high plasma LH and E 2 levels in azoospermic human patients [1,25]. The high plasma LH concentrations in the 4 azoospermic dogs were thought to be induced by a positive feed-back mechanism of the hypophyse-gonadal axis after lowered T secretion of the Leydig cells.…”
mentioning
confidence: 99%
“…There have been a few reports of abnormally high plasma LH and E 2 levels in azoospermic human patients [1,25]. The high plasma LH concentrations in the 4 azoospermic dogs were thought to be induced by a positive feed-back mechanism of the hypophyse-gonadal axis after lowered T secretion of the Leydig cells.…”
mentioning
confidence: 99%
“…There have been a few reports on azoospermic men with elevated plasma LH levels [1,12], and the function of There have been a few reports concerning hormone therapy for spermatogenic dysfunction in the dog [5,8]. While there have been cases in which hCG has been used to treat infertility in humans [6,13], there are no reports of it being used to treat infertility in male dogs.…”
mentioning
confidence: 99%
“…Therefore, attention was focused on the AR as a possible cause of the impaired spermatogenesis in subjects with idiopathic male infertility. It has long been postulated that defects in the AR gene can lead to partial or complete spermatogenic failure (Aiman et al 1979;Aiman and Griffin 1982) and more recently it has been shown that impaired function of the AR induces abnormalities in androgen action resulting in abnormal conditions such as androgen insensitivity syndrome (AIS) and infertility (Yong et al 2000).…”
Section: Discussionmentioning
confidence: 99%